Solar powered water pumping strategy for domestic use - Noorazimah Mat Alias (School of Environmental Engineering, University Malaysia Perlis, 2012)
Renewable energy of (Photovoltaic) solar powered pumps provides a welcome alternative to fuel-burning engines, windmills, and hand pumps. Therefore, the project will identify the potential of solar powered water pumping strategy for domestic water features. To be model the system of small scale solar pump 12V DC, it needed to designing and sizing the solar PV system. AutoCAD software is used for designing and drafting the circuit diagram. Meanwhile, for rating or sizing the system, it includes the step to take sizing of solar panel and battery as required. The main methodology of this project is to connect the entire component (solar panel, battery, water pump) and it involved the electrical wiring, soldering and piping work. After completion of the system in operation, it was tested by the two conditions, i.e. pumping water directly to the solar panel and pumping water through the battery. For parameter of project, the value of volume water flow rates, Q will be record in unit meter cubic per second (m3/s) to determine the capacity of solar pump. The reading is taken in different water head height for 1.0 m, 1.5 m, 2.0 m, 2.5 m and 3.0 m. Every height is recorded 3 reading and then compared the average. From the graft, it showed the value of water flow rate for pipe diameter inch cross section at 1m height is highest than other. As a conclusion, the solar water pumping have a big potential for application and it also identified needed of low maintenance.